A Summary of the Significance of Soil Materials Research on Land Ecologicalization. Issue 5 (February 2020) - Niu, Yan; Peng, Biao
Abstract: With the development of human society, a large number of land problems have emerged. These land problems seriously endanger human health and the ecological environment. Land engineering is based on solving land problems. The core is the study of soil organic remodeling. A key research direction of soil organic remodeling is material research. It can provide necessary support for the harmonious development of human-land relations and land ecologicalization.